Relationship between cone penetration test and undrained shear strength of soft soil - Ahmed Nasroulla, Nazaneen (2014)
Undrained shear strength of fine grain soil is one of the most important properties of soil in determining the soil stability especially in foundation design. This study presents the relationship between undrained shear strength and the fall cone parameter by using silly soil experienced an over consolidation ratio equal to two. The study focus to establish the relations between different cone angle of fall cone (ß), and the value of Hansbo`s (K) factor which is equal to (???????? ????2)/???? ) and the relationship between undrained shear strength and water content. A power relation was obtained for the relationship between different cone angle of fall cone (ß), and the value of k. The relations obtained in this study can be used to determine the value of liquid limit of fine grain soil by using different weight and cone angles at different depth of penetration of soft soil. Also the relationship between undrained shear strength and value of water content was established, which is indicate that the value of undrained shear strength decrease by increasing the water content of soil